RECRUITMENT STRATEGY TO HIRE THE BEST PEOPLE FOR ORGANIZATION - Dr. Ahmad Azmy, SE, MM (Journal of Management and Leadership, 2018)
This study aims to analyze recruitment strategies to fulfil human resource needs. This study uses theory and research results to explain the implications of the recruitment process to meet human resource needs.. Research result explain that the recruitment strategy starts by determining manpower planning which includes job design, job specification, and job description. The next process of determining recruitment strategies includes recruitment sources, recruitment methods, and recruitment stages. Positive implications of recruitment are high motivation, job satisfaction, and performance improvement. So the recruitment strategy is the main activity of human resource management to hire the best talent and own superior competence in achieving the business target of the company.